DETEKSI KECURANGAN LAPORAN KEUANGAN DI MASA PANDEMI COVID-19 DENGAN MODEL BENEISH M-SCORE DAN MODEL F-SCORE - isnawati isna; Lukman Effendy; Biana Adha Inapty (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2022)
The purpose of this study is to detect fraudulent financial statements committed by companies. This detection is carried out by 2 (two) methods, namely the Beneish M-Score method and the F-Score model. The Beneish M-Score model is a predictive model of financial statement fraud, the ratios contained in it have been proven to have the ability to predict financial statement fraud (Beneish, 1999). The F-Score is a measure used as a tool to detect material misstatements in financial statements (Pardosi, 2015). Data analysis of go-public companies in Indonesia listed in 2019 and 2020 was obtained from Osiris. The results of the study concluded that the average value of financial statement fraud decreased during the covid-19 pandemic, with an average decline of 74%. Paired t-test results are also shown in the sig value. (2-tailed) that the F-Score and M-Score calculations show a number greater than 0.05 which means that there is no significant difference in the F-Score and M-Score values ​​before and during the COVID-19 pandemic. It was concluded that the COVID-19 pandemic did not affect financial statement fraud in Indonesia.